2017
DOI: 10.1007/s00128-017-2159-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Abiotic Factors on Degradation of Imidacloprid

Abstract: The role of soil moisture, light and pH on imidacloprid dissipation was investigated. A high performance liquid chromatography (HPLC) based method was developed to quantify imidacloprid present in soil with a recovery of more than 82%. Rate of dissipation of imidacloprid from soil was faster in submerged condition compared to field capacity and air dried condition. Imidacloprid dissipated non-significantly between sterile and non-sterile soils, but at field capacity, the dissipation was faster in non-sterile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…LODs and LOQs were comparable to that of HPLC-ESI-MS/MS methods (1-20 ng/g) developed for food (pomegranate, coconut and wheat, etc.) residue analysis [31][32][33][34], but considerably lower than the methods based on HPLC-MS/MS, GC-ECD/MS and HPLC-UV (5-79 ng/g) for soil residue analysis [35][36][37].…”
Section: Analytical Performancementioning
confidence: 99%
“…LODs and LOQs were comparable to that of HPLC-ESI-MS/MS methods (1-20 ng/g) developed for food (pomegranate, coconut and wheat, etc.) residue analysis [31][32][33][34], but considerably lower than the methods based on HPLC-MS/MS, GC-ECD/MS and HPLC-UV (5-79 ng/g) for soil residue analysis [35][36][37].…”
Section: Analytical Performancementioning
confidence: 99%
“…More knowledge has been accumulated over the years about other neonicotinoids. Mahapatra et al [73] studied the effects of abiotic factors on the degradation of imidacloprid. They found that the rate of dissipation of imidacloprid from the soil samples was faster under submerged conditions compared to when the soil was left in its field capacity and soil samples were air-dried.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological degradation of these chemicals by the animal could also be rapid, bringing contamination levels below detection limits within days after exposure, especially if contamination levels are low (Klaassen and Watkins 2008). For example, imidacloprid was found to degrade to ~22.5% of starting levels after 25 days (Liu et al 2011) and ~50% after 60 days (Mahapatra et al 2017) of application, depending on environmental factors. Additionally, the absence of pesticides in our birds is likely not simply resulting from the technical capacity to detect them in biological tissues, as our minimal detectable limit (0.01 mg/kg; atrazine, clothianidin, and imidacloprid) and limit of quantification (0.8-2.05 mg/kg; glyphosate and AMPA) is well below what has previously been shown to cause toxicity in birds (Fishel 2005).…”
Section: Discussionmentioning
confidence: 99%